Kadar Protein Tempe Biji Labu Kuning (Cucurbita moschata) Dan Pemanfaatannya Sebagai Media Pembelajaran - Hasrina Hasrina; Musdalifah Nurdin (Universitas Tadulako, 2021)
Pumpkin seeds (Cucurbita moschata) in daily life is used only limited to pumpkin seed snack, whereas pumpkin seeds can be processed in various forms. One of them is pumpkin seed tempeh. Tempeh is a traditional fermented food rhizopus sp. made by fermentation and can be used as a food source that has economic value which has high protein. This study aims to determine the protein levels in pumpkin seed tempeh and its use as a learning media. The research type is an explorative descriptive research. Tempe pumpkin seeds were analyzed for protein levels by using micro Kjedhal analysis through three stages, namely destruction, distillation and titration as many as three repetitions. The results show the average protein level of pumpkin seed tempeh is 24.66%. Based on the results of validation tests by a team of experts in content, design and media as well as 20 students, the results of the study are very worthy to be used as a learning media in the form of posters with a feasibility percentage of 81.49%.